عہدِ نبوی کے معاشی اقدامات اور سماجی استحکام : عصری تناظر میں انطباقی مطالعہEconomic Measures and Social Stability in the Prophetic Era (SAW): An Adaptive Study in the Contemporary Context (Al-Qamar, 2024)
Before the advent of Islam, trade was the primary occupation of the people in Makkah. However, their commercial dealings often lacked ethical principles, leading to widespread exploitation. Deception, fraud, misrepresentation, and adulteration were common practices, resulting in economic injustices and fueling tribal and familial conflicts.In such circumstances, the Prophet Muhammad ﷺ introduced significant economic reforms, declaring all forms of trade unlawful that involved individual or collective harm. His approach aimed not only at preventing economic exploitation but also at fostering social stability by promoting generosity and compassion through charity and welfare initiatives.The Prophet ﷺ prioritized intellectual and moral training in economic matters. He emphasized ethical trade practices and their positive impact on society, advocating contentment over greed and reinforcing the belief that sustenance is a divine provision. These aspects will be explored in the study.Additionally, the research will highlight the benefits of interest-free financial transactions and their role in sustainable economic development. The study will also delve into the Prophet’s ﷺ directives regarding debt management, workers' rights, and financial policies that supported public welfare. By analyzing these measures, the paper will illustrate how adopting these principles in the modern era can lead to economic prosperity and stability, mirroring the successes witnessed during the Prophetic period and the era of the Rightly Guided Caliphs.
Keywords: The Prophetic Era ﷺ, Intellectual and Psychological Influences; Driving Forces; Economic and Social Stability; Ethical Trade Practices; Public Welfare; Contentment; Spiritual Fulfillment; Human Rights; and Financial System